Toxicity and Oviposition Deterrent Activities of Thyme Essential Oils against Anopheles arabiensis - Destaw Damtie; Yalemtsehay Mekonnen (Psyche: A Journal of Entomology)
Background. Malaria is one of the deadliest mosquito-borne diseases in sub-Saharan Africa and Ethiopia. Owing to their costs and environmental issues, synthetic insecticides are poor choices to control mosquitoes. Plant-based products can be considered as safe and biodegradable alternatives. The present study aimed to test the toxicity and oviposition deterrent activities of Thymus serrulatus and Thymus schimperi essential oils (EOs) against Anopheles arabiensis. Methods. Thyme EOs were extracted by hydrodistillation using the Clevenger-type apparatus. They were named Tar, Ala, and Yil after the areas of thyme collection Tarmaber, Alamata, and Yilmana Densa, respectively. Laboratory-based tests were used to determine the larvicidal, adulticidal, oviposition deterrent, and half lethal dose (LD50) of each EO. Results. The concentrations of 100 μl/L and 50 μl/L resulted in complete mortalities of larvae and adults, respectively, for all the three Eos considered. The EOs exhibited high repellency with oviposition activity index of −1 (OAI = −1) at concentrations of 50 μl/L (Tar), 100 μl/L (Ala), and 200 μl/L (Yil). Conclusions. The EOs of T. serrulatus and T. schimperi were effective against larvae and adult mosquitoes at small doses and resulted in oviposition deterrence at doses from 50 to 200 μl/L. Thus, these EOs are promising mosquitocides and oviposition deterrents. But, further tests both in the presence of already known and effective deterrents and field trials are required.